2023
DOI: 10.3390/solar3030021
|View full text |Cite
|
Sign up to set email alerts
|

Laser Activation for Highly Boron-Doped Passivated Contacts

Saman Sharbaf Kalaghichi,
Jan Hoß,
Renate Zapf-Gottwick
et al.

Abstract: Passivated, selective contacts in silicon solar cells consist of a double layer of highly doped polycrystalline silicon (poly Si) and thin interfacial silicon dioxide (SiO2). This design concept allows for the highest efficiencies. Here, we report on a selective laser activation process, resulting in highly doped p++-type poly Si on top of the SiO2. In this double-layer structure, the p++-poly Si layer serves as a layer for transporting the generated holes from the bulk to a metal contact and, therefore, needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…As detailed in Ref. [8], we found the linear dependence of the melt depth on H p in the laser processing of the poly-Si layers, which agrees with the same finding for the conventional laser processing of bulk c-Si [35,36]. This behavior enabled us to estimate the melt depth created by different H p [8].…”
Section: Highly Conductive Well-passivating P ++ -Poly-si/sio 2 Layerssupporting
confidence: 88%
See 4 more Smart Citations
“…As detailed in Ref. [8], we found the linear dependence of the melt depth on H p in the laser processing of the poly-Si layers, which agrees with the same finding for the conventional laser processing of bulk c-Si [35,36]. This behavior enabled us to estimate the melt depth created by different H p [8].…”
Section: Highly Conductive Well-passivating P ++ -Poly-si/sio 2 Layerssupporting
confidence: 88%
“…In contrast to the reactivation/healing process as discussed here, our previous study [8] showed that laser energy densities H p > H T led to increased iV OC values (in the first laser activation process). The observed difference originates from the thermal annealing step in the present process sequence (after laser activation).…”
Section: Highly Conductive Well-passivating P ++ -Poly-si/sio 2 Layerscontrasting
confidence: 73%
See 3 more Smart Citations